Aromanians/Vlachs in Greece: politics and identity - Nowicka-Rusek, Ewa (Balcanica Posnaniensia. Acta et studia, 2021)
The article shows different aspects of the Greek policy towards Vlach communities, important for their social and cultural activity. The case of Vlachs/Aromanians living in Greece is analyzed from the point of view of relatively large and functioning ethnic minority group, located within the Greek national majority. The Greek „republican concept of nationality”, included into the official policy, doesn’t accept ethnic/national minorities in the state. The article is created on the basis of long-lasting anthropological research, conducted by the author. It contains opinions expressed by Vlach/Aromanian intellectualists living in Greece, representing various concepts of Vlachness.